2021
DOI: 10.1007/s40429-021-00381-9
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Nicotine Delivery Systems (ENDS) Use and Pregnancy II: Perinatal Outcomes Following ENDS Use During Pregnancy

Abstract: Purpose of Review This review examines the risk of adverse perinatal outcomes following electronic nicotine delivery systems (ENDS) use during pregnancy, and considers whether there are sufficient data to support ENDS as a harm reduction approach during pregnancy. Recent Findings Seven papers assessed perinatal outcomes following ENDS use during pregnancy. There was evidence that ENDS use was associated with increased risk for some adverse perinatal outcomes (e.g., small for gestational age). However, the repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 90 publications
(92 reference statements)
0
4
0
Order By: Relevance
“… 38 Due to the lack of reliable evidence, there is broad consensus across public health agencies and professional organizations globally, that use of e-cigarettes should be avoided during pregnancy, regardless of smoking status and not be used as a harm reduction tool at this time. 38 - 40…”
Section: E-cigarettes and Harm Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 38 Due to the lack of reliable evidence, there is broad consensus across public health agencies and professional organizations globally, that use of e-cigarettes should be avoided during pregnancy, regardless of smoking status and not be used as a harm reduction tool at this time. 38 - 40…”
Section: E-cigarettes and Harm Reductionmentioning
confidence: 99%
“…DeVito, et al, reviewed 7 studies and found some preliminary data that e-cigarette use may be associated with poor perinatal outcomes, such as small for gestational age; however, there was insufficient data and small sample sizes which limited certainty of findings. 38 Due to the lack of reliable evidence, there is broad consensus across public health agencies and professional organizations globally, that use of e-cigarettes should be avoided during pregnancy, regardless of smoking status and not be used as a harm reduction tool at this time. [38][39][40] The existing evidence suggests exposure to toxicants and carcinogens from e-cigarettes is most likely less harmful than from combustible tobacco products.…”
Section: E-cigarettes and Harm Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Approximately 1.8% of Swedish women used snuff in pregnancy in 2021. 9 Whereas sufficient knowledge about nicotine exposure from electronic cigarettes in pregnancy still are lacking, 10,11 maternal snuff use has been associated with increased risk of stillbirth, preterm birth, neonatal apnea, and disturbed heart rate variability. [12][13][14][15] However, in contrast to smoking, snuff use has not been associated with increased risk of early neonatal mortality.…”
Section: Introductionmentioning
confidence: 99%